2012
DOI: 10.5267/j.msl.2012.09.028
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on relationship between residual income and internal and external performance measures

Abstract: During the past few years, there have been growing interest in learning the relationship between residual income and other financial figures such as dividend per share, market value and operating cash flow. The proposed study of this paper gathers the financial information of all listed firms traded in Tehran Stock Exchange over the period of 2007-2011. We only concentrate on listed companies whose fiscal years started from March to May of each year. The other criterion associated with the proposed study of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The results of this research showed that the independent variables investigated in this research had meaningful impacts on the research's dependent variable, which means that the impacts of company's systematic risk and markets risk on companies' stock return were positive. Daryani and Ahadi Serkani (2012), for instance, performed an investigation on relationship between residual income and internal and external performance measures for some listed firms traded in TSE over the period [2007][2008][2009][2010][2011]. The study used two regressions analysis and examined five hypotheses including the relationship between residual income and other factors including dividend per share, value added operating cash flow, value added cash flow, market cap and market value added.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this research showed that the independent variables investigated in this research had meaningful impacts on the research's dependent variable, which means that the impacts of company's systematic risk and markets risk on companies' stock return were positive. Daryani and Ahadi Serkani (2012), for instance, performed an investigation on relationship between residual income and internal and external performance measures for some listed firms traded in TSE over the period [2007][2008][2009][2010][2011]. The study used two regressions analysis and examined five hypotheses including the relationship between residual income and other factors including dividend per share, value added operating cash flow, value added cash flow, market cap and market value added.…”
Section: Introductionmentioning
confidence: 99%